Competitiveness of milk and wine production and processing in Albania - Martin Petrick; Catrin Schreiber; Peter Weingarten (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2004)
This study provides an empirical assessment of the competitiveness of Albanian dairy and wine production, based on specifically collected survey data. For both product groups, the analysis is carried out on two levels: farm level production of raw material and processing and manufacturing of the final product in the food industry. In a third step, both levels are aggregated to analyse the competitiveness of the entire production chain for each product group. Overall, the wine sector appears in an economically more favourable situation than the milk sector. Although there is currently no relevant export of wine, there has been considerable in-vestment activity at the farm level and the harmonisation of quality standards with EU legislation is currently pursued. Grape processing is currently profitable. Small farm and herd sizes limit the profitability and efficiency of dairy farming. Fragmented and dispersed production units increase the costs of milk collection. International quality standards are by far not met. This is partially due to the high share of informally traded milk and the importance of direct sales to consumers. It is therefore unlikely that Albanian dairy products will become internationally competitive in the near future. – – Die vorliegende Studie beinhaltet eine Einschätzung der Wettbewerbsfähigkeit der albanischen Milch- und Weinproduktion, die sich auf spezifisch gesammelte Betriebsdaten stützt. Für beide Produktgruppen wird eine Analyse auf zwei Ebenen durchgeführt: Erzeugung der Rohprodukte und Verarbeitungsstufe. In einem dritten Schritt werden die Teilergebnisse der beiden Ebenen zu einer Gesamtbewertung der Wettbewerbsfähigkeit der jeweiligen Produktions- und Verarbei-tungskette zusammengeführt. Insgesamt präsentiert sich der albanische Weinsektor in ökono-misch günstigerer Verfassung als der Milchsektor. Auch wenn der Export von albanischem Wein derzeit keine Rolle spielt, werden die notwendigen rechtlichen Rahmenbedingungen für die Sicherung von Qualität und Herkunftsbezeichnung bei Wein werden derzeit geschaffen. Auf der Erzeugerebene wurden in den vergangenen Jahren bereits größere Investitionen durchge-führt. Die Verarbeitungsstufe weist positive wirtschaftliche Ergebnisse auf. Milchproduktion und -verarbeitung leiden unter mangelnden Hygienestandards und einem stark informell ge-prägten, untransparenten Markt für Frischprodukte. Unter diesen Bedingungen fällt es den Mol-kereien schwer, sich wirtschaftlich zu behaupten. Es ist daher nicht zu erwarten, dass albanische Milchprodukte in nächster Zeit international wettbewerbsfähig sein werden.
urn:nbn:de:gbv:3:2-22503
Keywords: P23; Q12; Q13; 330; Agricultural sector; competitiveness; milk; wine; Albania; Agrarsektor; Wettbewerbsfähigkeit; Milch; Wein; Albanien